Analisis Maf'ul Muthlaq Berdasarkan Makna Dalam Al-Qur'an Juz 29 - D. Kadir, Sulemand; Hairuddin, Hairuddin (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This research discusses the meaning of maf’ul muthlaq in the Qur'an juz 29. The purpose of this study is to reveal the meanings of the maf’ul muthlaq sentence contained in the Qur'an juz 29. Maf'ul mutlaq is one of the rules explained in nahwu science as a complement to emphasize and strengthen (taukid). The purpose of this writing is to analyze the meanings in maf'ul mutlaq.  The method used is a qualitative method with a library research approach. The data source consists of primary and secondary data. The primary source is the qur'an juz 29 while the secondary source is the articles, books and sources related to the topic being studied. The results of the analysis show that in the Qur'an juz 29 which consists of 11 surahs maf'ul mutlaq which contains the type of affirmative meaning contained in surah al-haqqah verses 14, 44. Surah Noah verses 7, 17, and 18. Surah al-mudassir verse 14. Surah al-insan verses 6, 14, 23, and 28. Surah al-mursalat verses 2, 3, and 4. Explaining the meaning of quality (bayan li na'u) is found in al-haqqah verse 10, al-ma'arij verse 5, noah verses 9 and 22. Al-muzzamil verses 4, 8, 10, 10, 11, 16, and 20. While maf'ul mutlaq which explains the meaning of quantity (bayan lil adad) is only found in surah al-mulk verse 10.